Implementation of The Al-Quran Tahfidz Program to Form The Religious Character Students of SMAN 1 Pringgarata - Akhmad Husni; Syamsul Hakim; Sriharyati Sriharyati; Ahmada Eka Fathoni (Jurnal Ilmiah Profesi Pendidikan, 2023)
Education is carried out to shape the character of students. This research is a qualitative research. The objects of this research are all students of SMAN 1 Pringgarata for the 2023/2024 academic year. This research was conducted to determine the development of students in reading and memorizing the Koran. This research was carried out in three stages, namely the preparation, implementation and evaluation stages. The preparation stage is carried out to develop the method that will be applied in listening to students' memorization. The implementation stage includes the process of listening to the memorization and makhorijul letters in reading the Koran. The evaluation stage is carried out every mid-semester to determine student progress. The results of this research are in the form of qualitative data on students who routinely participate in murojaah activities every morning before entering class and memorize deposits once a week. After the activity was carried out, 90% of students were accustomed to reading the Koran every morning.